2008
DOI: 10.1590/s1516-89132008000700030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of kidney, liver and duodenum isolated from treated rats with Ginkgo Biloba extract and effects of this medicinal plant on the biodistribution of the padiopharmaceutical sodium pertechnetate

Abstract: Ginkgo biloba extract (EGb)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, authors have pointed out that in nuclear medicine, it is essential the understanding and quantification of this phenomenon in order to anticipate the behavior in vivo of radiotracers (Velasques de Oliveira et al, 2010b). In addition, authors have reported that several synthetic (Nigri et al, 2002) and natural medications (Moreno et al, 2007;Moreno et al, 2008a;Moreno et al, 2008b;Moreno et al, 2008c;Souza et al, 2011) are capable of interfering with the biodistribution and/or on the radiolabeling of blood constituents. These considerations show the importance of the studies about the effect of medications on the behavior of the radiopharmaceuticals.…”
mentioning
confidence: 99%
“…Moreover, authors have pointed out that in nuclear medicine, it is essential the understanding and quantification of this phenomenon in order to anticipate the behavior in vivo of radiotracers (Velasques de Oliveira et al, 2010b). In addition, authors have reported that several synthetic (Nigri et al, 2002) and natural medications (Moreno et al, 2007;Moreno et al, 2008a;Moreno et al, 2008b;Moreno et al, 2008c;Souza et al, 2011) are capable of interfering with the biodistribution and/or on the radiolabeling of blood constituents. These considerations show the importance of the studies about the effect of medications on the behavior of the radiopharmaceuticals.…”
mentioning
confidence: 99%